MANAJEMEN KELOMPOK ILMIAH REMAJA UNTUK MENUMBUHKAN KREATIVITAS INOVASI PEMBELAJARAN KEWIRAUSAHAAN SISWA SMK - Kartikaningsih Kartikaningsih; Tri Kuat; Muhammad Sayuti; Yoga Sahria (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Vocational education is not only concerned with preparing students to enter the workforce but also with developing their ability to generate ideas and identify entrepreneurial opportunities. In this context, this study examines the management of the Youth Scientific Club (Kelompok Ilmiah Remaja/KIR) at SMK Negeri 1 Panjatan and its contribution to fostering students’ entrepreneurial creativity and innovation. The study focuses on program planning, organizing, implementation, and evaluation through a descriptive qualitative approach with a single case study design. Data were collected through semi-structured interviews and document analysis. Six informants were selected using purposive sampling, comprising the principal, vice principal for student affairs, two KIR supervisors, and two students who actively participated in the program. The collected information was transcribed, reduced, thematically organized, and subsequently examined through source triangulation. The findings indicate that KIR management operates as an interconnected process. Planning is grounded in students’ interests and the school’s vision, while organizing facilitates cross-disciplinary collaboration. In practice, entrepreneurial innovation is developed through nine stages based on local potential. Evaluation is conducted continuously with support from school policies, facilities, and active participant involvement. This management pattern strengthens students’ creativity, self-confidence, and entrepreneurial innovation capabilities within an adaptive vocational education context. ABSTRAK Pendidikan vokasi tidak hanya berkaitan dengan kesiapan memasuki dunia kerja, tetapi juga dengan kemampuan peserta didik menciptakan gagasan dan peluang usaha. Dalam konteks tersebut, penelitian ini menelaah pengelolaan Kelompok Ilmiah Remaja (KIR) di SMK Negeri 1 Panjatan serta kaitannya dengan tumbuhnya kreativitas dan inovasi kewirausahaan siswa. Kajian diarahkan pada perencanaan, pengorganisasian, pelaksanaan, dan evaluasi program melalui pendekatan kualitatif deskriptif dengan desain single case study. Data dikumpulkan melalui wawancara semi-structured dan telaah dokumen. Enam informan dipilih menggunakan teknik purposive sampling, yakni kepala sekolah, wakil kepala sekolah bidang kesiswaan, dua guru pembimbing KIR, dan dua siswa yang aktif mengikuti kegiatan. Informasi yang diperoleh ditranskripsikan, direduksi, dikelompokkan secara tematik, kemudian diperiksa melalui triangulasi sumber. Temuan memperlihatkan bahwa pengelolaan KIR berjalan sebagai rangkaian yang saling terhubung. Perencanaan berangkat dari minat siswa dan visi sekolah, sedangkan pengorganisasian membuka kolaborasi lintas keahlian. Pada pelaksanaannya, inovasi kewirausahaan dikembangkan melalui sembilan tahapan berbasis potensi lokal. Evaluasi dilakukan secara berkelanjutan dengan dukungan kebijakan, fasilitas, dan keterlibatan peserta. Pola pengelolaan tersebut memperkuat kreativitas, kepercayaan diri, dan kemampuan inovasi kewirausahaan siswa dalam konteks pendidikan vokasi yang adaptif.